AUT841197_Lay_Abstract – Supplemental material for The therapeutic alliance in cognitive-behavioral therapy for school-aged children with autism and clinical anxiety ... - Klebanoff, Sami M; Kashia A Rosenau; Wood, Jeffrey J (SAGE Journals, 2019)
Supplemental material, AUT841197_Lay_Abstract for The therapeutic alliance in cognitive-behavioral therapy for school-aged children with autism and clinical anxiety by Sami M Klebanoff, Kashia A Rosenau and Jeffrey J Wood in Autism ...